Exploring the Effectiveness of Songs for Learning Improvement: A Case of Elementary Level Students’ English Skills - Olga A. Rorintulus; Ceisy N. Wuntu (Universitas Muhammadiyah Enrekang, 2023)
This research study explores the effectiveness of incorporating songs into the English language learning curriculum for elementary-level students, focusing on their impact on various language skills. In an educational landscape that increasingly emphasizes creative and engaging approaches, this investigation delves into the potential benefits of integrating songs into traditional language instruction. This study was a descriptive qualitative study, while the data is collected through classroom observations and literature studies in order to provide a comprehensive view of the multifaceted effects of using songs as a pedagogical tool. The findings highlight the positive influence of songs on vocabulary acquisition, pronunciation refinement, and listening comprehension development. Additionally, songs contribute to a richer cultural context for language learning, fostering greater cultural awareness among elementary students. Importantly, the research underscores the motivational power of songs, which enhances student engagement and willingness to participate actively in English language activities. This research concludes that integrating songs into the curriculum is a promising strategy for enhancing English language skills at the elementary level. It advocates for a thoughtful and strategic approach to song selection and pedagogical methods while recognizing the need for continued exploration and research to refine the implementation of songs in language education. Ultimately, this study underscores the value of creative and engaging learning methods in nurturing well-rounded language skills among young learners.